The Efficacy of Chlorhexidine Gel as an Adjunctive Treatment for Patient with Chronic Periodontitis - Ban Zuhair Ahmad (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: chronic Periodontitis is considered to be an inflammatory disease and is characterized by the damaging the connective tissue and supporting bone due to secondary infection by periodontal bacteria. Chlorhexidine has been used in the dental practice as an excellent antiplaque agent. Chlorhexidine not only exhibits special property of substantivity, it also possesses a broad antimicrobial spectrum which makes its use in wide variety of oral disorders. Virtually all disciplines of dentistry make use of this material in different formulations like mouth wash, gel, spray, varnish, and restorative material.Aims of study: The aim of this study was to evaluate the clinical effectiveness of locally delivered Chlorhexidine gel as an adjunctive therapy to scaling and root planing in treatment of chronic periodontitis.Material and methods: five patients with chronic periodontitis were selected. Pocket depth between 4 and 6 mm was selected and the patient had two sites on his mouth (splitting mouth). A total of 17 control sites were scaled and root planed and 17 test sites were scaled and root planed and Chlorhexidine gel was added. The clinical parameters, probing depth (PD), clinical attachment level (CAL), plaque index (PI) and bleeding on probing (BOP), gingival index were recorded at baseline, 1 week, 2 weeks and 4 weeks.Results: From baseline to a period of 4 weeks, significant difference was found between test and control group for PD, CAL, PI and BOP.Conclusions: Subgingival injection of Chlorhexidine gel adjunct with scaling and root planing appeared to cause significant improvement compared with scaling and root planing alone in persons with chronic periodontitis.